2022
DOI: 10.3389/fvets.2022.878162
|View full text |Cite
|
Sign up to set email alerts
|

Dog Owners' Ideas and Strategies Regarding Dental Health in Their Dogs-Thematic Analysis of Free Text Survey Responses

Abstract: Periodontal disease is the most common disease in dogs over 3 years of age. In dogs, as in humans, daily tooth brushing, as a means of active dental home care, is considered the gold standard for prophylaxis and prevention of periodontal disease progression. However, the performance of adequate tooth brushing is insufficient in dogs. There is no full account as to why dog owners fail to comply with this routine, but in order to facilitate better practice, a further understanding of dog owner's perspectives is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…According to this survey study, the most common reason for inadequate dental home care routines is insu cient cooperation between the dog and the owner, which also agrees with previous ndings by the same research group where 79% of Swedish dog owners reported that the dog is unwilling towards dental inspection, leading to di culties [14]. Additionally, dog owners' self-perceived di culties with tooth brushing were seen in a thematic analysis as a hindrance to good dental health, and a need for increased knowledge and support was also suggested [20]. There is thus a need for practical teaching in this regard.…”
Section: Adherencesupporting
confidence: 89%
“…According to this survey study, the most common reason for inadequate dental home care routines is insu cient cooperation between the dog and the owner, which also agrees with previous ndings by the same research group where 79% of Swedish dog owners reported that the dog is unwilling towards dental inspection, leading to di culties [14]. Additionally, dog owners' self-perceived di culties with tooth brushing were seen in a thematic analysis as a hindrance to good dental health, and a need for increased knowledge and support was also suggested [20]. There is thus a need for practical teaching in this regard.…”
Section: Adherencesupporting
confidence: 89%
“…Аналіз анкетування власників, проведений Enlund et al (2020) Всупереч науковим результатам, власники тварин впевнені, що відмінний стан зубів забезпечують дієта та згодовування кісток, що є хибною думкою. Тому потрібні подальші дослідження щодо визначення факторів ризику стоматологічних хвороб та розробки стратегій підтримки здоров'я ротової порожнини залежно від породи, розмірів та віку (Enlund et al, 2022).…”
Section: вісник сумського національного аграрного університетуunclassified
“…Daily dental home care, such as brushing, prevents and controls PD in people and dogs. Even though a manual, an ultrasonic toothbrush, a nylon glove, and a microfiber finger cloth help clean the teeth, daily brushing is difficult [ 10 ].…”
Section: Introductionmentioning
confidence: 99%